Knowledge systems and networks for nutrition in India: A review - McGrath, Louise; Kunaratnam, Yaso; Anuradha, T. N. (International Food Policy Research Institute, 2014)
The first part of this review provides an overview of the current nutrition knowledge landscape in India based on the secondary research conducted on the existing knowledge systems and networks catering to nutrition-based information needs of policymaking audiences in India. The second section of the report shares the outcomes of face-to-face interviews conducted with the conveners of these knowledge networks. It also shares the findings from the interviews with decisionmakers and program implementers and impressions of these networks from a user perspective.